Aspects of translation in psychological and psychiatric cross-cultural research - Drennan, Gerard (Department of Psychology, 2015)
This study investigates the process of translating English-language questionnaires and interview formats into Black African languages. The details of translation are invariably glossed in reports and publications on the use of translated psychological and psychiatric instruments. This results in a lack of clarity on how these translated instruments are produced and what difficulties are encountered in their development and use, suggesting the need for a detailed examination of the translation process. Researchers working in South Africa were interviewed with a semi-structured format in 1989. Extracts of the data gathered in eleven interviews is presented here with a focus on two aspects of the translation process. Firstly, problems in the evaluation of translation quality and the interpretation of the successful use of a translation are identified. It appears that theoretical confusion results in the under-utilisation of the opportunity for translation quality evaluation presented by translation strategies. An additional exploration of discourses tacit in the use of translated instruments with interpreters, and a consideration of the role of power and resistance in these contexts is undertaken. Secondly, a rationale for researchers' use of different types of translators is presented. Unexamined assumptions about cultural expertise implicit in the decision-making process associated with translation are identified. Recommendations are made as to areas that require further research and clarification.